2012
DOI: 10.1100/2012/384936
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes Do Not Transdifferentiate into Proper Osteoblasts

Abstract: Recent publications suggested that monocytes might be an attractive cell type to transdifferentiate into various cellular phenotypes. Aim was, therefore, to evaluate the potential of blood monocytes to transdifferentiate into osteoblasts. Monocytes isolated from peripheral blood were subjected to two previously published treatments to obtain unique, multipotent cell fractions, named programmable cells of monocytic origin (PCMOs) and monocyte-derived mesenchymal progenitor cells (MOMPs). Subsequently, MOMPs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…and ). Schmitt et al reported similar results in 2012 and in contrast their experiments indicated that PCMOs may differentiate into osteoclasts if cultured in the presence of osteogenic stimuli . One reason for this could be the low CD90 expression as found by our FACS analysis.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…and ). Schmitt et al reported similar results in 2012 and in contrast their experiments indicated that PCMOs may differentiate into osteoclasts if cultured in the presence of osteogenic stimuli . One reason for this could be the low CD90 expression as found by our FACS analysis.…”
Section: Discussionsupporting
confidence: 68%
“…On the other hand M‐CSF and RANKL were used for the in vitro generation of osteoclasts . So it is not surprising that PCMOs tend to differentiate into osteoclasts and osteoclasts were shown to accelerate the osteogenic differentiation of MSCs in vitro . Preliminary results of our group indicate an increase of osteoclastic marker genes (MMP‐9, CALCR2, TRACP5) during PCMO dedifferentiation phase.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Following overnight adherence, medium was changed to dedifferentiation medium (Alpha MEM, 10% FCS, 2 mM l -glutamine, 100 U/ml penicillin, 100 μg/ml streptomycin, 2.5 ng/ml rhM-CSF) for 6 days. Osteoclast differentiation was induced by differentiation medium (Alpha MEM, 10% FCS, 2 mM l -glutamine, 100 U/ml penicillin, 100 μg/ml streptomycin, 20 ng/ml rhRANKL) for 21 days (Schmitt et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Signals were normalized to relative cell numbers by Resazurin conversion. Trap5B staining was performed as described (Schmitt et al, 2012). …”
Section: Methodsmentioning
confidence: 99%